Glass Science and its Applications - Nandyala Sooraj Hussain (2010)
The proceedings contain 6 papers. The topics discussed include: optimization of ormosil glasses for luminescence based dissolved oxygen sensors; optical analysis of RE3+: boro-fluoro-phosphate glasses; splicing and coupling losses in hollow-core photonic crystal glass fibers; study of structure and Li+ ions dynamics in presence of Fe2O3 in Bi2O3a(r)B2O3 glasses; structural and optical analysis of RE3+: LiNbO3 ceramic powders; and application of glass reinforced hydroxyapatite composite in the treatment of human intrabony periodontal angular defects aˆ two case reports.